2011
DOI: 10.1161/strokeaha.110.602441
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Hypertrophy and Muscle Myostatin Reduction After Resistive Training in Stroke Survivors

Abstract: Background and Purpose-Stroke survivors experience disproportionate muscle atrophy and other detrimental tissue composition changes on the paretic side. The purpose was to determine whether myostatin levels are higher in paretic vs nonparetic muscle and the effects of resistive training (RT) on paretic and nonparetic mid-thigh muscle composition and myostatin mRNA expression in stroke survivors. Methods-Fifteen stroke survivors (50 -76 years) underwent bilateral multi-slice thigh CT scanning from the knee to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 41 publications
(46 reference statements)
6
94
0
Order By: Relevance
“…It should be appreciated that following SCI, muscle is paralyzed, and that there is little neuromuscular stimulation of muscle innervated by motor neurons originating in spinal segments below the level of the spinal cord injury. Following stroke, paralyzed muscle atrophies and expresses elevated levels of cytokines such as TNF-␣ and, potentially, myostatin, and increased neuromuscular activity attenuates these abnormalities (38,39). It may well be that similar abnormalities are present in paralyzed skeletal muscle after SCI; in support of this possibility, preliminary studies have indicated that in male rats, mRNA levels for TNF-␣ and IL-6 are elevated in gastrocnemius muscle after SCI.…”
Section: Reloading Bone Through Muscle Contractions Elicited By Es Inmentioning
confidence: 99%
“…It should be appreciated that following SCI, muscle is paralyzed, and that there is little neuromuscular stimulation of muscle innervated by motor neurons originating in spinal segments below the level of the spinal cord injury. Following stroke, paralyzed muscle atrophies and expresses elevated levels of cytokines such as TNF-␣ and, potentially, myostatin, and increased neuromuscular activity attenuates these abnormalities (38,39). It may well be that similar abnormalities are present in paralyzed skeletal muscle after SCI; in support of this possibility, preliminary studies have indicated that in male rats, mRNA levels for TNF-␣ and IL-6 are elevated in gastrocnemius muscle after SCI.…”
Section: Reloading Bone Through Muscle Contractions Elicited By Es Inmentioning
confidence: 99%
“…studies of paralyzed muscle after stroke or nerve injury. In stroke patients, myostatin mRNA levels were increased in the vastus lateralis from the paretic versus non-paretic side and were reduced by resistance training (Ryan et al, 2011). In studies of rodents that have examined skeletal muscle after nerve transection or nerve crush, there have been persistent elevations of myostatin protein in some studies, but only a transient increase reported in others (Baumann et al, 2003;Lima et al, 2009).…”
Section: Fig 4 Effects Of Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…Myostatin signals by binding the activin receptor IIB, ultimately resulting in phosphorylation and nuclear translocation of the transcription factors Smad2 and Smad3 (Glass, 2010). Myostatin mRNA levels have been reported to be increased in muscle paralyzed by stroke (Ryan et al, 2011). How myostatin levels and downstream signaling are altered after SCI is not well understood.…”
mentioning
confidence: 99%
“…The improvement in muscle strength after TOT could be attributed to an increase in muscle volume56 and recruitment of alternative neural substrate 57. Ryan and colleagues reported that 12 weeks of resistive training of the knee extensors increased the paretic thigh's cross‐sectional area and volume by ≈15% and increased the knee extension strength by 56% 56. Luft and colleagues57 reported that 6 months of treadmill exercise induced greater activation in multiple brain regions than passive stretching in subjects with stroke.…”
Section: Discussionmentioning
confidence: 99%